7 5 - Ամյակին ԱՌՆՈ ԲԱԲԱՋԱՆՅԱՆ. «Եթե ես կոմպոզիտոր չլինեի...» - Աշոտի Առաքելյան, Գուրգեն (Musical Armenia, 2011)
Ministry Of Culture, Youth And Sport RA, USSR (1980-1985), Editor-in-chief of the journal “Soviet Union Culture” (1996-1997) Gurgen A. Araqelyan writes his memories about Arno Babajanyan in the article “If I weren’t a composer”, based on the interview with the composer. The article is dedicated to the 75th birth anniversary of the composer.